Spatial–temporal assessment of hydrocarbon biodegradation mechanisms at a contaminated groundwater site in Serbia. Issue 2 (7th February 2022) - Marić, Nenad; Štrbački, Jana; Polk, Jason; Slavković Beškoski, Latinka; Avdalović, Jelena; Lješević, Marija; Joksimović, Kristina; Žerađanin, Aleksandra; Beškoski, Vladimir P.
ABSTRACT: The characterization and cleanup of groundwater contamination in hazardous-waste sites are of significant engineering and scientific importance. This study analyzes biodegradation fingerprints in groundwater, 25 years after the accidental leakage of kerosene (jet fuel) at the site in central Serbia. The long-term existence of hydrocarbon contamination and the presence of indigenous microbiological populations capable of biodegradation have been confirmed by the results of GCxGC-MS chromatography and microbiological characterization. Total petroleum hydrocarbons (TPH), geochemical indicators, and other parameters were spatially analyzed to provide insight into biodegradation occurrence. The lowest concentrations of electron acceptors (O2, NO3 -, and SO4 2- ) and the highest concentrations of microbial metabolic products (Mn and Fe) overlap in the piezometers closest to the source of contamination, due to the occurrence of different biodegradation mechanisms. Based on the analysis of redox-sensitive compounds, the mixed oxic-anoxic processes in groundwater also correspond to the aforementioned zone, as confirmed by the redox potential (Eh) measurements. The results of cross-study analysis reveal further reduction of hydrocarbon contamination, the occurrence of less anoxic redox processes, and the increase of oxic conditions in groundwater. Overall, the results provide clear evidence of the biodegradation effects in groundwater and insight into their evolution under natural attenuation processes.